Anion-mediated approach to overcome oxidation in ether electrolytes for high-voltage sodium-ion batteries - Xingyu Wang; Qi Fan; Ziheng Liu; Xinyue Zhu; Mei Yang; Zhiyuan Guo; Yuting Chen; Liuqi Wang; Yu Jing; Hui Xia (Nature Communications)
Abstract The ether-based electrolytes are acknowledged for their compatibility with a diverse array of sodium-ion battery anodes, as well as their capability to enable efficient and reversible electrochemical reactions. However, they encounter a challenge of oxidation at high voltages. We find that a standard diglyme-based electrolyte starts to oxidize and break down at voltages exceeding 3.9 V (vs. Na+/Na). This deterioration is attributed to the nucleophilic nature of the diglyme solvent and the presence of oxygen atoms that possess two unpaired electrons. To address this issue, we incorporate foreign anions into the electrolyte system to passivate the reactive sites of terminal H on diglyme solvents, inhibiting further dehydrogenation and oxidation during battery operation. The constructed cathode electrolyte interphase, enriched with NaF and NaNxOy, substantially boosts the oxidation resistance of electrolyte to over 4.8 V (vs. Na+/Na), expanding the stability window and rendering it feasible for various high-voltage cathode materials. Our approach also ensures compatibility with either hard carbon or commercial graphite anodes, guaranteeing operation in pouch cells. This study elucidates the relationship between interfacial chemistry and oxidation tolerance at high voltages, offering an approach to the development of practical ether-based electrolytes for high-energy-density battery technologies.